Gender differences in latin-american patients with rheumatoid arthritis (2012)
Background: Data on the effect of gender in rheumatoid arthritis (RA) in non-Caucasian populations is scarce. Latin America and the Caribbean (LAC) is a large population with unique characteristics, including high admixture. Objective: Our aim was to examine the effect of gender in patients with RA in LAC. Methods: This was a 2-phase study. First we conducted a cross-sectional and analytical study in which 1128 consecutive Colombian patients with RA were assessed. Second, a systematic review of the literature was done to evaluate the effect of gender in LAC patients with RA. Results: Our results show a high prevalence of RA in LAC women with a ratio of 5.2 women per man. Colombian women with RA are more at risk of having an early age at onset and developing polyautoimmunity and abdominal obesity, and they perform more household duties than their male counterparts. However, male gender was associated with the presence of extra-articular manifestations. Of a total of 641 potentially relevant articles, 38 were considered for final analysis, in which several factors and outcomes related to gender were identified. Conclusions: RA in LAC women is not only more common but presents with some clinical characteristics that differ from RA presentation in men. Some of those characteristics could explain the high rates of disability and worse prognosis observed in women with RA in LAC. © 2012 Elsevier HS Journals, Inc.